2004
DOI: 10.1002/glia.20040
|View full text |Cite
|
Sign up to set email alerts
|

Distinct types of astroglial cells in the hippocampus differ in gap junction coupling

Abstract: Previous studies have shown that two subpopulations of cells with astrocytic properties coexist in the mouse hippocampus, which display distinct morphological and functional characteristics, specifically a nonoverlapping expression of either AMPA-type glutamate receptors (GluR cells) or glutamate transporters (GluT cells). Use of transgenic mice with hGFAP promoter-controlled EGFP expression and patch-clamp recordings allow reliable identification of the two cell types in hippocampal slices. Extending function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
3
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(189 citation statements)
references
References 31 publications
(47 reference statements)
8
176
3
2
Order By: Relevance
“…To clarify whether RG-like cells express Cx43, we used a transgenic approach. Cx43 fl/ϩ /hGFAP-Cre/hGFAP-EGFP mice (p90) were generated expressing ␤-galactosidase (␤-Gal) under control of regulatory elements of the Cx43 gene in hGFAP-Crepositive cells (17), allowing indirect analysis of Cx43 expression in hGFAP-EGFP-positive cells (Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…To clarify whether RG-like cells express Cx43, we used a transgenic approach. Cx43 fl/ϩ /hGFAP-Cre/hGFAP-EGFP mice (p90) were generated expressing ␤-galactosidase (␤-Gal) under control of regulatory elements of the Cx43 gene in hGFAP-Crepositive cells (17), allowing indirect analysis of Cx43 expression in hGFAP-EGFP-positive cells (Fig. S4).…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicate that, in this brain region characterized by a strong anatomofunctional neuronal compartmentalization, astrocytes also exhibited a specific spatial organization and are constituted by several subpopulations with distinct coupling properties favoring intercellular communication within the barrel rather than between two neighboring barrels. In the septa, uncoupled astrocytes exhibit passive electrophysiological properties suggesting that in the somatosensory cortex, in contrast to the hippocampus (Matthias et al, 2003;Wallraff et al, 2004, there are subpopulations of PAs with different coupling properties.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in many brain regions and throughout animal life, gap junctional communication (GJC) is extensive and widespread between subpopulations of astrocytes (D'Ambrosio et al, 1998;Blomstrand et al, 2004;Wallraff et al, 2004). Such communicating pathways are provided by junctional proteins named connexins (Cxs), members of a multigenic family (Theis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GluR cells completely lack gap junction coupling, whereas the GluT cells are extensively coupled. 75 Electron microscopic studies have identified synapse-like structures onto GluR cells and receive spontaneous synaptic inputs from GABAergic and glutamatergic neurons in acute hippocampal slice preparations. 76 The GluR cell described previously also closely resembles a cell type identified as a third class of macroglia and variously named as neuron glia-2 (NG2) cells, oligodendrocyte precursor cells, polydendrocytes, synantocyte, or complex cells.…”
Section: Astrocyte Typesmentioning
confidence: 99%